Design Integrated Crop-Livestock and Fish Farming Model with LEISA System in North Minahasa Regency - Jolyanis Lainawa; Tilly F. D. Lumy; Eusebius K. M. Endoh (AIBPM Publisher, 2024)
Agricultural land in North Minahasa district has been shrinking. The number of farming families with land ownership of less than 0.5 ha is increasing due to land fragmentation. Designing an integrated farming system (IAS) model is a solution to the land problem, so that intensive farming can be carried out. This system can also be a solution to self-sufficiency and food self-sufficiency in agricultural products in a sustainable manner. The purpose of the study was to analyse the integrated farming system between crops, livestock and fish with various integrated farming patterns based on land area feasibility, economic feasibility, ecological feasibility, social feasibility for farming development in North Minahasa district. The results of the analysis obtained that the land area for crops and livestock/fish is between 0.2 ha to 0.4 ha including 0.1 ha for housing and other household businesses. economically, the net income from crops and livestock/fish is at least an average of Rp 175,000 per day. (North Sulawesi UMP 2023 standard, IDR 3,485,000/month), with a ratio of net income to RTP needs ≥ 1.0. Ecologically, the production of organic matter from livestock/fish is sufficient/exceeds the needs of crops (≥ 1.0) The strategic model for SPT development in North Minahasa district is to increase the variety of farmer income sources, increase the use of organic matter from livestock and agricultural residues, optimise land and soil utilisation